A fossil caddisfly (Insecta: Trichoptera) from the Eocene of Colorado - Robinson, Jason L.; Thomas, M. Jared; Heads, Sam W. (Zootaxa, 2018)
A new genus and species of fossil caddisfly (Insecta: Trichoptera) from the Lower Eocene (Ypresian) Green River Formation of Colorado is described. Litholimnephilops yinani gen. et sp. nov. is the first adult caddisfly to be described from the Green River Formation, and is characterized by large adult body size, presence of ocelli, dark leg spines, and a lack of terminal crossveins in the anterior anastomosis region of the forewings. Terminal genitalia are not visible in the preserved specimen. Familial placement is uncertain, though similarities with the families Limnephilidae and Phryganeidae are observed.